2013
DOI: 10.4018/jea.2013010104
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Online Stock Trading Service Adoption

Abstract: Globalization and recent advancement in the deployment of Internet and related technologies, have significantly transformed all sectors of the modern economy. For instance, electronic service has enabled the application of Internet platform in stock trading, thereby empowering individuals across diverse location to engage in trading activities. As established by extant theories on technology acceptance, individuals are expected to exhibit different attitude and behaviour towards new technology. This study aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…The study found that when e-investors' expectations regarding the system's perceived security are satisfied, their trust is increased and they are more likely to use these online services, especially if the system is successful in achieving their goals. Trust may be used as a tactical variable, in accordance with Abroud (2012), to lessen the risk associated with conducting business in an uncertain environment. Similar findings have been made by Lee (2009a), Abroud (2012), Abroud et al (2013), Bhuvanam and Mohan (2015), and Maziriri, Mapuranga, and Madinga (2019).…”
Section: Perceived Privacymentioning
confidence: 99%
See 3 more Smart Citations
“…The study found that when e-investors' expectations regarding the system's perceived security are satisfied, their trust is increased and they are more likely to use these online services, especially if the system is successful in achieving their goals. Trust may be used as a tactical variable, in accordance with Abroud (2012), to lessen the risk associated with conducting business in an uncertain environment. Similar findings have been made by Lee (2009a), Abroud (2012), Abroud et al (2013), Bhuvanam and Mohan (2015), and Maziriri, Mapuranga, and Madinga (2019).…”
Section: Perceived Privacymentioning
confidence: 99%
“…Trust may be used as a tactical variable, in accordance with Abroud (2012), to lessen the risk associated with conducting business in an uncertain environment. Similar findings have been made by Lee (2009a), Abroud (2012), Abroud et al (2013), Bhuvanam and Mohan (2015), and Maziriri, Mapuranga, and Madinga (2019). These studies found that investor PT had a significant positive impact on the desire to invest in online trading platforms.…”
Section: Perceived Privacymentioning
confidence: 99%
See 2 more Smart Citations
“…Main theories used to explain Information and Communication Technology (ICT) adoption at the individual level are Technology Acceptance Model (TAM, Davis, 1989;Davis, Bagozzi, & Warshaw, 1989), Theory of Planned Behaviour (TPB, Ajzen, 1985Ajzen, , 1991, Innovation Diffusion Theory (IDT, Rogers, 1995), and Unified Theory of Acceptance and Use of Technology (UTAUT, Venkatesh, Morris, Davis, & Davis, 2003). These theories have been extensively used to explain individuals' acceptance and use of an ICT (Knudsen & Roman, 2015;Ramayah, Chiun, Rouibah, & May, 2014;Shih, 2013;Alwahaishi & Snášel, 2013;Abroud, Choong, & Muthaiyah, 2013;Ko & Lu, 2012;Islam, 2011).…”
Section: Introductionmentioning
confidence: 99%